Effects of Including Agricultural Products in the Customs Union between Turkey and the EU: A Partial Equilibrium Analysis for Turkey - Harald Grethe (Peter Lang International Academic Publishers, 2004)
The inclusion of agricultural products in the current customs union is one of the potential future steps on the road to further political and economic integration between Turkey and the EU. This book examines the effects of such integration of agricultural markets on the Turkish agricultural sector as well as on consumers and the Turkish budget. Results are compared to alternative options for Turkish agricultural policy. To this aim, a detailed partial equilibrium model of the Turkish agricultural sector is developed. The complete liberalization of the agricultural sector is found to lead to significant welfare gains compared to the maintenance of current policies. It appears that including agricultural products in the customs union results in similar results with few but significant exemptions.
Keywords: 330